Drug Repurposing by Siderophore Conjugation: Synthesis and Biological Evaluation of Siderophore‐Methotrexate Conjugates as Antibiotics - Zhao, Sheng; Wang, Zhi‐Peng; Lin, Zihua; Wei, Guoxing; Wen, Xumei; Li, Siyu; Yang, Xiaohong; Zhang, Qun; Jing, Chunmei; Dai, Yuanwei; Guo, Jian; He, Yun (Angewandte Chemie International Edition, 2022)
Drug repurposing is considered a promising strategy to fight antimicrobial resistance (AMR). Methotrexate (Mtx), a classical anticancer drug, could strongly inhibit bacterial dihydrofolate reductase (DHFR). However, its poor permeability into bacteria and potent human cytotoxicity make it unsuitable as an antibacterial. Herein, we reported the conjugation of Mtx with a siderophore to construct “Trojan horse” antibacterials. The most potent conjugate 8 with nanomolar minimum inhibitory concentration (MIC) values exhibited over 1.00×103‐fold improved activity against Gram‐positive Streptococcus pneumoniae (S. pneumoniae) and Gram‐negative Yersinia enterocolitica (Y. enterocolitica) compared with Mtx, while possessing 2.31×103‐fold reduced human cytotoxicity, resulting in 2.08×106‐fold improvements in the therapeutic index. This proof‐of‐principle study verifies that siderophore conjugation is an effective strategy for developing new antibacterials from anticancer drugs. The conjugation of methotrexate (Mtx) with a siderophore to construct “Trojan horse” antibacterial conjugates is reported. The most potent conjugate exhibited over 1000‐fold improved activity against Gram‐positive Streptococcus pneumoniae and Gram‐negative Yersinia enterocolitica compared with Mtx, while possessing 2313‐fold reduced human cytotoxicity, resulting in 2.08×106‐fold improvements in the therapeutic index.